The Impact of Stress and Anxiety on Dysmenorrhea Severity: A systematic review - Abdulkhaliq, Mohammed Sobh; Alshahrani, Mashael Abdullah; Alamri, Ghadi Mohammad A; Aldawodi, Reema Mohammed; Memish, Halah Ahmad; Asiri, Sohaila Ahmed; Alqahtani, Arwa Awad; Ashahrani, Maram Ali M; AlQahtani, Razan H.; Alrimthi, Yusra Hasan; Alzahrani, Saeed Ali M; Jaber, Zarah Qasem (Saudi Medical Horizons Journal, 2025)
Primary dysmenorrhea (PD) affects a significant proportion of menstruating individuals, with stress and anxiety increasingly recognized as modifiable factors influencing pain severity. This systematic review synthesizes evidence on the relationship between stress/anxiety and dysmenorrhea severity, exploring underlying mechanisms and clinical implications. Following PRISMA guidelines, we conducted a comprehensive search across PubMed, Web of Science, Scopus, and ScienceDirect. Included studies assessed stress (perceived stress, PTSD, occupational stress) or anxiety (generalized/trait anxiety) in individuals with PD, using validated scales. Risk of bias was evaluated using the Newcastle-Ottawa Scale and Cochrane RoB 2.0. Of 2,305 screened records, 45 studies met inclusion criteria, with 13 analyzed in detail. Cross-sectional studies (n=12) predominated, alongside one RCT study. Significant associations between stress/anxiety and PD severity (e.g., OR=2.8 for perceived stress (95% CI: 1.9–4.1); r=0.782, p<0.001 for stress-pain correlation). PTSD and occupational stress exacerbated dysmenorrhea (β=10.48, p=0.001; p <0.05, respectively). Neurobiological mechanisms (e.g., amygdala hypertrophy, HPA axis dysfunction) were implicated in pain amplification. Stress and anxiety are significantly associated with dysmenorrhea severity, potentially mediated by neuroendocrine and inflammatory mechanisms.